Living in the climate crisis: Exploring situated perspectives and openings for change through everyday life stories - Bennetsen, Nina Moesby (Politik, 2019)
Stories and narratives have been used in social scientific research for decades, to entail perspectives of the lived experiences in different contexts. In this article, I argue that everyday life stories of situated experiences can contribute with rich understandings of different experiences, possibilities for change, or abilities to respond to the climate crisis. The article is based on theories from within urban studies, everyday life sociology, feminist theory and scholars engaged with stories in in social sciences.